2015
DOI: 10.1139/apnm-2014-0287
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle architectural adaptations to marathon run training

Abstract: We assessed lateral gastrocnemius (LG) and vastus lateralis (VL) architecture in 16 recreational runners before and after 12 weeks of marathon training. LG fascicle length decreased 10% while pennation angle increased 17% (p < 0.05). There was a significant correlation between diminished blood lactate levels and LG pennation angle change (r = 0.90). No changes were observed in VL. This is the first evidence that run training can modify skeletal muscle architectural features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
0
24
1
1
Order By: Relevance
“…These results cannot be explained by the strategy mentioned above. It should be noted that the three studies observed a decrease in the fascicle length 55,58,59) . Inter-and intra-muscle differences in the changes in pennation angle were also confirmed 45,68,71,84) .…”
Section: Evidence For Pennation Angle Changementioning
confidence: 83%
See 3 more Smart Citations
“…These results cannot be explained by the strategy mentioned above. It should be noted that the three studies observed a decrease in the fascicle length 55,58,59) . Inter-and intra-muscle differences in the changes in pennation angle were also confirmed 45,68,71,84) .…”
Section: Evidence For Pennation Angle Changementioning
confidence: 83%
“…Overall, training-induced increases in fascicle length are accompanied by an increase in muscle size (muscle hypertrophy, which is defined as an increase in muscle fiber area, muscle thickness, anatomical crosssectional area or volume in this article), although four studies failed to find muscle hypertrophy 45,52,54,55) and two studies did not show the data on muscle size 56,57) . Two studies observed a decrease in fascicle length of the gastrocnemius with 58) and without 59) muscle hypertrophy, and Timmins et al 55) showed a decrease in the fascicle length of BF without muscle hypertrophy. It should be noted that some reports 43,45) calculated fascicle length as the muscle thickness divided by the sine component of the pennation angle determined by small probe width, which could involve a large error 14) .…”
Section: Longitudinal Study Evidence For Fascicle Length Changementioning
confidence: 97%
See 2 more Smart Citations
“…Most ultrasound studies of gastrocnemius muscle architecture have assessed changes related to aging and to resistance training . There has been a single study reporting a 17% increase in pennation angle and 10% decrease in fascicle length, with no hypertrophy in the GL following a 12‐week marathon training program . It has been suggested that the stimulus for architectural adaptations is not sufficient in endurance running due to the low load, high volume nature of ultradistance running training .…”
Section: Introductionmentioning
confidence: 99%